Establishment and Application of a Real-Time Recombinase Polymerase Amplification Assay for the Detection of Avian Leukosis Virus Subgroup J - Qu, Guanggang; Li, Yun; Zhao, Zhongwei; Miao, Lizhong; Wei, Feng; Tang, Na; Xu, Qingqing; Nair, Venugopal; Yao, Yongxiu; Shen, Zhiqiang (Frontiers in Veterinary Science, 2022)
Avian leukosis caused by avian leukosis virus（ALV), belonging to the genus Alpharetrovirus of the Family Retroviridae, are associated with benign and malignant tumors of different hemopoietic cells in poultry. Currently, there are many detection methods developed for detection of ALV, however, many of these methods are not suitable for rapid on-site testing, due to the limitations on the instruments or the relative low sensitivity. Herein we describe the development of real-time recombinase polymerase amplification (RT-RPA) assay for rapid detection of ALV subgroup J (ALV-J). The major viral structural glycoprotein gp85, used as the molecular target for the RT-RPA assay, was highly specific for the subgroup. The results were obtained within 20 min at 38℃, with the detection sensitivity of 100 copies/μl of standard plasmid pMD18-T-gp85 as the template. Evaluation of the specificity of RT-RPA showed that there was no cross-reaction with other avian viruses. Of the 50 clinical samples tested, RT-RPA assay showed a correlation rate of 92% with routine PCR, while 12 commercial vaccine samples showed 100 % correlation with routine PCR. The developed real-time ALV-J assay shows promise for rapid and sensitive detection of ALV-J in diagnostic laboratories and suitable for on-site detection, especially in resource-poor environment and thus facilitating the prevention and control of ALV-J.